2015 IEEE International Conference on Robotics and Automation (ICRA) 2015
DOI: 10.1109/icra.2015.7139540
|View full text |Cite
|
Sign up to set email alerts
|

Feedforward augmented sliding mode motion control of antagonistic soft pneumatic actuators

Abstract: Soft pneumatic actuators provide many exciting properties, but controlling them without the use of bulky and expensive flow-control valves can be difficult and computationally expensive. We seek a solution to this problem by introducing an inexpensive and reliable muscle-like linear soft actuator used antagonistically to operate a rigid 1-DoF joint, resulting in a system that combines the advantages of rigid and soft robotics. Using this setup, we performed precise motion control using a sliding mode feedback … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…We previously demonstrated that average pressure inside soft actuation chambers can be regulated through pulse width modulation (PWM) using valves [1]. The segment is driven by two actuation chambers.…”
Section: Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously demonstrated that average pressure inside soft actuation chambers can be regulated through pulse width modulation (PWM) using valves [1]. The segment is driven by two actuation chambers.…”
Section: Controlmentioning
confidence: 99%
“…To control the curvature of the bending actuator, we adapted an iterative sliding mode controller from [1], the final control law of which is given as:…”
Section: Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Similarly, we developed extensile fiber reinforced soft actuators called reverse pneumatic artificial muscles (rPAMs) that relieve contractile stresses upon pressurization to apply antagonistic forces on underlying kinematic chains with large displacement ranges. 18,19 If bending deformation is required (for a snake-like robot 15 ), a semi-circular cross-sectional area is used as well as an inextensible (e.g. fabric, plastic, paper) thin constraint layer on the flat edge such that axial stresses are converted to bending deformations 20 as shown in Figure 1.…”
Section: Actuation: Modular Multi-materials Composite Soft Pneumatic Amentioning
confidence: 99%
“…30 Compared to traditional electromechanical actuation, our soft actuators are low-bandwidth systems, which increases the burden on control to achieve precise positioning, although the inherent safety of soft robotic systems compensates for small positioning errors without resulting in large contact forces. To decouple potential sources of error due to sensing difficulties in a soft body, we studied motion control on sensorized bench-top rigid kinematic modules, including a simple revolute joint operated by two antagonistic fluidic soft muscles, 18 and more recently, a 2-DoF universal joint module operated by three fluidic soft muscles 31 as shown in Figure 5-A. For operation, these muscles articulating the module are connected to a pressure source and each controlled by a separate miniature fast-response solenoid valve.…”
Section: Control: Robust Sliding Mode Motion Control Of Soft Robotic mentioning
confidence: 99%